ECR 플라즈마에 의한 알루미늄 질화처리시 표면조도의 영향 - 김진수(Jin-Soo Kim); 안재현(Jae-Hyun Ahn); 고경헌(Kyung-Hyun Ko); 오수기(Soo-Ghee Oh) (Biuletyn Uniejowski, 1991)
Microstructure evolution during low temperature vapor deposition exhibits wel-developed columnar structure mainly owing to geometrical shadowing effect of surface roughness. It is concluded that this structure is concided with many theoretical models suggested so far. In case of aluminum nitride film deposition consisted of etching and nitriding step employing ECR plasma, the rougher the surface before etching, the finer and more cone-and-whisker structure can be developed. In turn, this fine structure affects the formation and growth of columnar as well as offers many sites available for mechanical lock-up. Conclusively, the formation of well-defined columnar structures depends on the initial surface roughness.